First Nations and Aboriginal Counsellor Education - Morrissette, Patrick J. (Canadian Counselling and Psychotherapy Association, 2007)
This paper discusses contextual issues unique to First Nations and Aboriginal (FNA) undergraduate counsellor education. Although FNA and non-FNA student counsellors share similar educational experiences and needs, significant differences between these two groups require consideration and accommodation. This paper explores important features that influence student learning including student acclimatization, learning styles and participation, and the disclosure of cultural information. Cet article traite de questions contextuelles propres à la formation universitaire de premier cycle de conseillers des Premières nations et autochtones. Bien que les étudiants conseillers autochtones et non autochtones partagent des expériences et des besoins éducatifs similaires, des différences significatives entre ces deux groupes exigent la prise en considération et l'accommodation. L'auteur examine certains facteurs importants qui influencent l'apprentissage de ces étudiants, y compris le degré d'adaptation, les styles d'apprentissage et la participation à celui-ci, ainsi que la divulgation d'information d'ordre culturel.